2013
DOI: 10.1002/jez.b.22486
|View full text |Cite
|
Sign up to set email alerts
|

Mesoteloblast‐Like Mesodermal Stem Cells in the Polychaete Annelid Platynereis dumerilii (Nereididae)

Abstract: Spiral cleavage is observed in animals that belong to the lophotrochozoa, a large group of marine invertebrates. As characteristic for spiral cleavage, the bulk of mesoderm forms from one cell, the "4d blastomere." This process has not yet been followed in cellular detail in annelids except in the leech, where "mesoteloblasts," a pair of mesodermal stem cells, generate two bands of mesoderm precursor cells in an iterative fashion. It is so far unknown whether such stem cell-like lineage is a general property o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 42 publications
4
53
0
Order By: Relevance
“…Additional work was carried out by their counterparts in Europe (e.g., Heymons, 1893;Wierzejski, 1905). That early work has been extended in recent decades using modern cell-autonomous lineage tracers for a number of species (i.e., the gastropod molluscs Crepidula fornicata and C. convexa, Hejnol et al, 2007;Lyons et al, 2012, and Ilyanassa obsoleta, Render 1991, 1997Chan and Lambert 2014; the polyplacophoran mollusc, Chaetopleura apiculata, Henry et al, 2004; the nemerteans, Cerebratulus lacteus, Carinoma tremaphoros, Maslakova et al, 2004a,b; the polyclad turbellarian Hoploplana inquilina, Boyer et al, 1996Boyer et al, , 1998; and the annelids Capitella teleta, , Meyer and Seaver, 2009, 2010, and Platynereis dumerilii, Ackerman et al, 2005Fischer and Arendt, 2013). Together, this body of work has revealed that the ultimate fates of these quadrants are, to a large extent, homologous across the embryos of different spiralian phyla.…”
Section: (B) Though All Four Macromeres Are Capable Of Becoming 3dmentioning
confidence: 99%
“…Additional work was carried out by their counterparts in Europe (e.g., Heymons, 1893;Wierzejski, 1905). That early work has been extended in recent decades using modern cell-autonomous lineage tracers for a number of species (i.e., the gastropod molluscs Crepidula fornicata and C. convexa, Hejnol et al, 2007;Lyons et al, 2012, and Ilyanassa obsoleta, Render 1991, 1997Chan and Lambert 2014; the polyplacophoran mollusc, Chaetopleura apiculata, Henry et al, 2004; the nemerteans, Cerebratulus lacteus, Carinoma tremaphoros, Maslakova et al, 2004a,b; the polyclad turbellarian Hoploplana inquilina, Boyer et al, 1996Boyer et al, , 1998; and the annelids Capitella teleta, , Meyer and Seaver, 2009, 2010, and Platynereis dumerilii, Ackerman et al, 2005Fischer and Arendt, 2013). Together, this body of work has revealed that the ultimate fates of these quadrants are, to a large extent, homologous across the embryos of different spiralian phyla.…”
Section: (B) Though All Four Macromeres Are Capable Of Becoming 3dmentioning
confidence: 99%
“…These cells express the gene vasa (Rebscher et al, 2007) and comprise the primordial germ cells of the worm as well as the precursors of the mesodermal teloblasts. Fischer and Arendt (2013) have determined that the embryonic precursors to the mesodermal teloblasts undergo a series of stereotyped asymmetric cell divisions to produce first the primordial germ cells and subsequently the precursor cells of the mesoderm of the 3-segment larva in the same way as the leech M teloblasts. The injection of the 2d lineage, homologous to the DNOPQ lineage of the leech has not been carried out to date in Platynereis.…”
Section: A New Comprehensive Definition Of Annelid Teloblastsmentioning
confidence: 99%
“…Yet, in mollusks, the mesodermal bands have generally been described as mostly less extensive and rather short lived, especially when compared to the situation in annelids (Korschelt and Heider, 1936; Raven, 1966; Fioroni, 1971, 1992; Wanninger and Wollesen, 2015). In the worm‐shaped solenogasters, however, the mesodermal bands seem to acquire larger dimensions and persist for a considerable period of time–a condition, which is more similar to other spiralians, especially annelids (e.g., Mead, 1897; Schmidt, 1925; Okada, 1940; Anderson, 1959, 1966, 1973; Goto et al., ’99; Ackermann et al., 2005; Seaver et al., 2005; Dill et al., 2007; Woodruff et al., 2007; Fischer and Arendt, 2013). Furthermore, the situation we observed is in agreement with classical descriptions on mesoderm formation and differentiation of solenogasters and polyplacophorans (Pruvot, 1890, 1892; Heath, 1899; Naef, 1924; Hammarsten and Runnström, 1925; Baba, 1938; Thompson, 1960; Salvini‐Plawen and Bartolomaeus, 1995) but is demonstrated here for the first time over the entire course of development using state‐of‐the‐art techniques.…”
Section: Discussionmentioning
confidence: 99%